Strategy to adopt diverse food trees in agriculture to improve food and nutrition - CGIAR Research Program on Forests, Trees and Agroforestry (2020)
A fruit tree portfolio approach developed by ICRAF that can be scaled to inform policies for sustainable intensification of fruit production to meet food and nutrient gaps, based on national food-based dietary guidelines. The strategy has been taken up by next users through the implementation of several development projects based on the food tree portfolio concept.